Corazón resiliente: una aproximación a la afección cardiaca en Covid prolongado - Parra-Lucares, Alfredo; Ávila C., Cristián; Mallol S., Manuel; Villa U., Eduardo (Revista Hospital Clínico Universidad de Chile, 2024)
The post-Covid-19 pandemic period has raised several questions regarding the new conditions associated with SARS-CoV-2 infection, one of which is the so-called long Covid. Among its characteristics, cardiac involvement stands out as a central element of this new pathology. From a pathophysiological perspective, there are different mechanisms through which this condition could be triggered, either directly due to the subacute inflammation of the initial hyperinflammatory disease, or indirectly, associated with the activation of autoimmune mechanisms. Clinical manifestations encompass a spectrum of symptoms and signs associated with major cardiological syndromes, such as palpitations, dyspnea, dizziness, or angina. Each of these symptoms reflects the involvement of different cardiac structures, grouped into manifestations of the conduction system, heart failure, cardiomyopathy, pericarditis, and acute or chronic coronary heart disease, respectively. To date, the existing literature on the diagnosis, treatment, and prognosis of these different conditions is limited, based on the identification of predictors derived mainly from retrospective observational studies. Similarly, recommendations are grounded in the extrapolation of previous knowledge in the field. We pose the question of whether prolonged Covid will be considered a new